Metabolic Profiles of Serum and Ovarian Tissue in Taihe Black-Boned Silky Fowl During the Early and Peak Laying Periods - Xuan Huang; Shibao Li; Zhaozheng Yin (Animals)
Egg production is a complex biological process closely linked to ovarian development and metabolic adaptation in laying hens. As the core reproductive organ, the ovary undergoes significant changes during different egg-laying stages. This study employed untargeted metabolomics to analyze metabolites in serum and ovarian tissues of hens at 20W and 30W. The results revealed that metabolic reprogramming in ovarian tissues was more pronounced than in serum. Shared metabolites between serum and ovarian tissues demonstrated coordinated interactions between systemic and local metabolic networks. The synthesis of prostaglandin E1 during lipid metabolism was identified as a key driver of ovulation and hormone production. Extracellular matrix remodeling and polyamine metabolism, particularly spermidine/spermine, enhanced cell adhesion and antioxidant capacity during ovarian development. These findings provide new insights into follicular development, ovulation regulation, and steroid hormone biosynthesis, while suggesting potential metabolic targets to improve poultry reproductive efficiency.